Sex-related differences in the association between migraine, COVID-19, and long COVID: a population-based cohort - Al-Hassany, Linda; MaassenVanDenBrink, Antoinette; Kurth, Tobias (Frontiers in Neurology, 2025)
BackgroundCoronavirus disease 2019 (COVID-19), caused by the SARS-CoV-2 virus, placed unprecedented pressure on public health systems due to its mortality and global panic—and later due to long COVID challenges. One of these long COVID symptoms, headache, often resembles migraine-like features. Migraine shares similarities with COVID-19 and long COVID, yet the influence of sex is understudied. Our primary objective was to study the interrelationship between COVID-19 and migraine prevalence, while considering sex differences. The secondary objective was to examine how long COVID symptoms (headache, anosmia, memory, and concentration problems) affect males and females with and without COVID-19 and migraine.MethodsAll analyses were conducted using Lifelines, a prospective cohort study in the northern Netherlands. Baseline characteristics (2006–2014), self-reported migraine diagnoses (until 2021), and questionnaires on COVID-19 and long COVID symptoms (2020–2022) were collected. Logistic regression analyses were conducted to study the association between lifetime migraine and current SARS-CoV-2 infections while adjusting for age, sex, diet, educational attainment, activity, and smoking. Descriptive and sex-stratified analyses were conducted on long COVID symptoms.ResultsA total of 150,507 individuals were included, of which 29,680 (19.7%) reported migraine and 120,827 (80.3%) not. A total of 1,867 individuals with migraine [6.3% of individuals with migraine, 44.0 years (IQR 36.1–50.3)] and 6,797 individuals without migraine [5.6% of individuals without migraine, 44.4 years (IQR 35.3–52.2)] reported to be SARS-CoV-2 infected. The majority of individuals with migraine consisted of females (77.0% of those with migraine vs. 54.0% of those without migraine). The adjusted odds of having SARS-CoV-2 infections was 6.3% higher among those with (a history of) migraine compared with individuals without migraine in the logistic regression model (OR = 1.06, 95% CI 1.01–1.12). A slightly higher OR was observed in females (OR = 1.08, 95% CI 1.02–1.15), and the association was not apparent in males (OR = 1.00, 95% CI 0.88–1.12). Secondary analyses revealed that individuals with both migraine and COVID-19, and females in particular, were the most frequently bothered by long COVID symptoms headache, anosmia, concentration, and memory problems. Individuals with none of these diseases were the least bothered.ConclusionsIndividuals with migraine, especially females, are slightly more likely to report and/or contract COVID-19. Those with both conditions report long COVID symptoms more frequently, suggesting a shared vulnerability or pathophysiology. This may indicate the need for clinical surveillance of migraine patients recovering from COVID-19.